EMPIRICAL INVESTIGATION OF TOURIST SATISFACTION AMONG DOMESTIC AND FOREIGN VISITORS WITH CULTURAL HERITAGE SITES IN HUE CITY, VIETNAM - THANH HA, THAI (ASEAN Journal on Hospitality and Tourism, 2005)
This paper presents the findings from the empirical investigation of comparison on tourist satisfaction among domestic and international visitors with cultural heritage sites in Hue city, Vietnam. Interviews were equally made to a total sample of 120 international and domestic tourist respondents. Statistical paired-sample tests, factor analysis and multiple regressions were conducted to identify the difference as well as the relationship between the expectation and overall satisfaction among the international and domestic tourists with the four cultural heritage sites of Citadel; Thien Mu Pagoda; Tu Duc; and Khai Dinh King Tombs at Hue city.The research reveals that the satisfying attributes were different among domestic and foreign tourists and demographic characteristics had an impact on the overall satisfaction. Implications were drawn and future research was proposed.